Food and Masculinity in Contemporary Autobiographies Cast-Iron Man - Pascual Soler, Nieves (Palgrave Studies in Life Writing, 2018)
This book is concerned with food autobiographies written by men from the 1980s to the present. It concentrates on how food has transformed autobiographical narratives and how these define the ways men eat and cook nowadays. After presenting a historical overview of the place of food within men ́s autobiography, this volume analyzes the reasons for our present interest in food and the proliferation of life narratives focused on cooking. Then it centers around the identities that male chefs are taking on in the writing of their lives and the generic models they use: the heroic, the criminal and the hunting autobiographical scripts. This study gives evidence that autobiographies are crucial in the redefinition of the new masculinities emerging in the kitchen. It will appeal to readers interested in Food Studies, Autobiographical Studies, Men's Studies and American Literature and Culture.